New Implant Design with Midcrestal and Apical Wing Thread for Increased Implant Stability in Single Postextraction Maxillary Implant - Antonio Scarano; Bartolomeo Assenza; Francesco Inchingolo; Filiberto Mastrangelo; Felice Lorusso (Hindawi Limited, 2019)
Background. The immediate placement of a dental implant could represent an option treatment for the rehabilitation of a postextractive missing tooth socket to replace compromised or untreatable teeth, with the advantage of single-session surgery. In this way, the anatomy of the alveolar bone defect, the preservation of the buccal cortical bone, and the primary stability of the fixture represent the critical factors that consent a precise implant placement. Objective. This case report describes a novel fixture design for postextractive alveolar socket immediate implant. Methods. Two patients (25 and 31 years old) were treated for postextractive dental implant placement to replace both central upper incisor teeth with four implants. The residual bone implant gap was not filled with graft or bone substitute. The restoration was provided following a standard loading protocol by a cement-sealed prosthetic abutment. Results. Clinically, all implants positioned showed an excellent insertion torque. No postoperative complications were reported. At 6 months of healing, the buccal cortical bone and the implant stability were present and well maintained. Conclusion. The evidence of this study allows us to underline the possible advantages of this new fixture design for postextractive implant technique.